Sistem Pakar Untuk Mendiagnosa Penyakit Diabetes Menggunakan Metode Inferensi Fuzzy Mamdani - Suharni Bacin (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2021)
Expert system is a system that has a role to help the work role of an expert where the system can work like an expert. Diabetes is a disease that is very often found in the community, this disease is caused by heredity or from an unhealthy diet. The diabetes expert system is useful for diagnosing a disease with diabetes or not, where this early diagnosis is useful for providing treatment or prevention of the disease. Mamdani fuzzy inference method which is used to diagnose diabetes in expert systems using fuzzy functions in the diagnosis process